Intravenous ondansetron for the prevention of supine hypotensive syndrome during spinal anesthesia for cesarean section: a randomized controlled trial - Zhang, Yuan; Xiao, Fen; Zhang, Wangping (Frontiers in Pharmacology, 2024)
Background: Supine hypotensive syndrome is a common complication in late pregnancy. This study aims to explore the effects of ondansetron for the prevention of supine hypotensive syndrome during spinal anesthesia for cesarean section. Methods A total of 80 women undergoing elective cesarean delivery were randomly assigned to two groups (the ondansetron group and the control group), with 40 cases in each group. The ondansetron group received 0.075 mg/kg of ondansetron intravenously 5 minutes before induction of spinal anesthesia; the control group was given the same volume of saline solution. The blood pressure and heart rate were measured. Umbilical artery pH was analyzed, and the incidence of nausea and vomiting and vasoconstrictor drugs usage were noted. Results The incidence of supine hypotensive syndrome, nausea and vomiting, and vasoconstrictor drugs use were significantly lower in the ondansetron group than the control group (2.5% vs.20%, P = 0.029; 2.5% vs.22.5%, P = 0.007; 5% vs.22.5%, P = 0.012, respectively). Umbilical artery pH was higher in the ondansetron group than the control group, and statistical significance was observed (7.31±0.03 vs 7.28± 0.04, P = 0.002). The maternal hemodynamic parameters and the neonatal Apgar score were similar between the 2 groups. Conclusions Ondansetron can effectively prevent supine hypotensive syndrome, reduce the incidence of nausea, vomiting and vasoconstrictor drugs use, and improve neonatal umbilical arterial pH during spinal anesthesia for cesarean section.